Editors' Choice—Electrocatalyzed Oxygen Reduction at Manganese Oxide Nanoarchitectures: From Electroanalytical Characterization to Device-Relevant Performance in Composite Electrodes. Issue 11 (8th September 2018) - Ko, Jesse S.; Parker, Joseph F.; Vila, Mallory N.; Wolak, Mason A.; Sassin, Megan B.; Rolison, Debra R.; Long, Jeffrey W.
Abstract : We assess the effect of the pore–solid architecture of cryptomelane-type manganese oxide (MnO x ) xerogels and aerogels on electrocatalysis of the oxygen-reduction reaction (ORR) using three different electrochemical test platforms. Rotating-disk electrode measurements at ink-cast films of carbon + MnO x show that both MnO x nanoarchitectures exhibit comparable intrinsic ORR activity for four-electron reduction with a low onset overpotential (∼310 mV). The MnO x xerogel and aerogel powders were also incorporated into practical powder–composite electrodes that include carbon and polymer binder. When evaluated in an air-breathing three-electrode electroanalytical cell, the aerogel-based composite electrode exhibits an overpotential lowered by ∼50 mV compared to the xerogel-based analog. The superior performance of the aerogel-based composite is also demonstrated in zinc–air button cells, with up to 100 mV improvement in discharge voltage at moderate-to-challenging current densities (5–125 mA cm –2 ). We ascribe the enhanced activity of the MnO x aerogel-based composite to a more uniform dispersion of the aerogel powder within the carbon/binder matrix, as verified by focused-ion beam−scanning electron microscopy and elemental mapping. The results reported herein highlight the importance of assessing the translation of electrocatalytic activity from fundamental measurements to technologically relevent electrode structures.